2016
DOI: 10.1177/1557988315596225
|View full text |Cite
|
Sign up to set email alerts
|

Ever and Annual Use of Prostate Cancer Screening in African American Men

Abstract: Since prostate cancer continues to disproportionately affect African American men in terms of incidence, morbidity, and mortality, prostate-specific antigen (PSA) screening plays an important role in early detection, especially when men engage in informed decision making to accept or decline this test. The authors evaluated utilization of PSA testing among African American men based on factors that are important components of making informed decisions. Utilization of PSA testing was evaluated based on whether … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 39 publications
(44 reference statements)
0
18
0
Order By: Relevance
“…Multiple studies have shown a significant association of physician communication and receipt of PSA testing. 16, 25, 26 In a small community-based cohort study from the Philadelphia area, 64% of men reported ever having a PSA test and 57% reported a PSA test within the prior year. 25 The overall likelihood of PSA testing was associated with physician communication, and recent testing was strongly associated with health insurance status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have shown a significant association of physician communication and receipt of PSA testing. 16, 25, 26 In a small community-based cohort study from the Philadelphia area, 64% of men reported ever having a PSA test and 57% reported a PSA test within the prior year. 25 The overall likelihood of PSA testing was associated with physician communication, and recent testing was strongly associated with health insurance status.…”
Section: Discussionmentioning
confidence: 99%
“…16, 25, 26 In a small community-based cohort study from the Philadelphia area, 64% of men reported ever having a PSA test and 57% reported a PSA test within the prior year. 25 The overall likelihood of PSA testing was associated with physician communication, and recent testing was strongly associated with health insurance status. In a larger study utilizing SEER-Medicare data, independent factors associated with PSA screening among Black men aged 40–99 were higher education level, regular access to a healthcare provider, and a health care provider recommendation for PSA screening.…”
Section: Discussionmentioning
confidence: 99%
“…PCa diagnosis involves prostate-specific antigen (PSA) screening ( American Academy of Family Physicians, 2017 ; American Cancer Society, 2017 ; Halbert et al, 2017 ; Han et al, 2013 ; Moyer, 2012 ; Powell, Vigneau, Bock, Ruterbusch, & Helibrun, 2014 ; Saltzman et al, 2015 ; Shen & Kumar, 2016 ; Siegel et al, 2017 ). Circulating serum PSA levels are considered abnormal when detected above 4 ng/ml ( American Academy of Family Physicians, 2017 ; Moyer, 2012 ).…”
mentioning
confidence: 99%
“…ACS includes AA men in the high-risk category and recommends repeated annual PCa screening for men with PSA levels >2.5 ng/ml ( American Cancer Society, 2017 ). While informed decision-making is the current recommendation for PCa screening, recent studies highlight that AA men may not be making informed decisions about PCa screening ( Davis et al, 2010 ; Feng et al, 2013 ; Halbert et al, 2017 ; Han et al, 2013 ; Hoffman et al, 2009 ; Leyva et al, 2016 ; McCormack et al, 2009 ). This is largely due to patients having limited knowledge of PCa screening and providers either not offering sufficient up-to-date information or not asking patients about their preferences ( Davis et al, 2010 ; Hoffman et al, 2009 ; Leyva et al, 2016 ; McCormack et al, 2009 ).…”
mentioning
confidence: 99%
“…A growing body of literature documents factors associated with African American men’s decisions to undergo prostate cancer screening ( Pedersen, Armes, & Ream, 2012 ). In general, men with higher levels of income, education, insurance coverage, and those with a family member who has been diagnosed with the disease are more likely to be screened than their counterparts ( Halbert et al, 2015 ; Harmon, 2014 ; Pedersen et al, 2012 ; Sanchez, Bowen, & Hart, 2007 ). Other factors that may impact African American men’s screening decisions include lack of awareness of heightened risk of the disease ( Shavers, Underwood, & Moser, 2009 ; Shaw, Scott, & Ferrante, 2013 ), diminished access to health care ( Forrester-Anderson, 2005 ), mistrust of health-care providers, ( Allen, Stoddard, & Sorenson, 2007 ; Spain, Carpenter, Talcott, 2008 ), and poor communication with health-care providers ( Allen et al, 2007 ; Halbert et al, 2015 ; Hughes, Sellers, Fraser, Teague, & Knight, 2007 ; Shaw et al, 2013 ).…”
mentioning
confidence: 99%